Measurement and microscopic description of odd–even staggering of charge radii of exotic copper isotopes - De Groote, R. P.; Billowes, J.; Binnersley, C. L.; Bissell, M. L.; Cocolios, T. E.; Goodacre, T. Day; Farooq-Smith, G. J.; Fedorov, D. V.; Flanagan, K. T.; Franchoo, S.; Ruiz, R. F. Garcia; Gins, W.; et al. (Nature Physics, 2020)
Nuclear charge radii globally scale with atomic mass number A as A1∕3, and isotopes with an odd number of neutrons are usually slightly smaller in size than their even-neutron neighbours. This odd–even staggering, ubiquitous throughout the nuclear landscape1, varies with the number of protons and neutrons, and poses a substantial challenge for nuclear theory2–4. Here, we report measurements of the charge radii of short-lived copper isotopes up to the very exotic 78Cu (with proton number Z = 29 and neutron number N = 49), produced at only 20 ions s–1, using the collinear resonance ionization spectroscopy method at the Isotope Mass Separator On-Line Device facility (ISOLDE) at CERN. We observe an unexpected reduction in the odd–even staggering for isotopes approaching the N = 50 shell gap. To describe the data, we applied models based on nuclear density functional theory5,6 and A-body valence-space in-medium similarity renormalization group theory7,8. Through these comparisons, we demonstrate a relation between the global behaviour of charge radii and the saturation density of nuclear matter, and show that the local charge radii variations, which reflect the many-body polarization effects, naturally emerge from A-body calculations fitted to properties of A ≤ 4 nuclei.
CRIS-Team Scopus Importer:2020-05-02